Restoration of Constitutional Alignment in TKA with a Novel Osteotomy Technique - Wang, Zhibing; Cheng, Xingwang; Zhang, Yuan; Zhang, Xia; Zhou, Yue (The Journal of Knee Surgery, 2020)
Many studies have shown that restoration of the preoperative constitutional varus may lead to a normal knee status in total knee arthroplasty (TKA). It is also known that coronal femoral lateral bowing contributes to constitutional varus of the femoral shaft, and bilateral femoral lateral bowing (BFLB) can decelerate medial knee osteoarthritis progression. In this sense, the BFLB should be reserved in TKA. To date, no study has yet reported the technique to reserve BFLB in TKA. Our study showed that the proximal and distal femur had no significant geometric difference between patients with varus knees and BFLB (> 5°) and volunteers with healthy knees and straight femoral shaft. So, the virtual center of femoral head fell on the distal femoral mechanical axis (DMA) after accurate correction of the bowing, indicating that the DMA should be the femoral original constitutional mechanical axis (CA). Subsequently, the distal femoral osteotomy was performed perpendicular to DMA in TKA, and the postoperative angle formed by DMA and tibial mechanical axis (TMA) was measured to assess whether CA was restored successfully. In this study, the gap balance was achieved without medial collateral ligaments release, and the patient's CA was successfully restored (range of DMA–TMA angle 178.2°–179.9°). This study provides a novel technique to restore preoperative CA in patients with varus knees and BFLB. It is found that the distal femur should be cut perpendicular to DMA, so the lower limb alignment and soft tissue strains can be restored to the preoperative state, and the knees would be stable and in a natural status after TKA.
Keywords: total knee arthroplasty; coronal femoral lateral bowing; virtual center of femoral head; distal femoral mechanical axis; constitutional alignment